Associations between T cells and attention problems in the general pediatric population: The Generation R study - Kirsten I. M. Looman; Charlotte A. M. Cecil; Christina Grosserichter‐Wagener; Jessica C. Kiefte‐de Jong; Menno C. vanZelm; Henriëtte A. Moll (Wiley, 2021)
Abstract Objective The pathogenesis of attention‐deficit/hyperactivity disorder (ADHD) is currently unclear. We hypothesized that chronic immune activation, as indexed by T and B cells, plays a role in the pathophysiology of attention problems. Therefore, we examined T and B cell subsets in a general pediatric population with information on attention problems. Methods We included 756 10‐year‐old children from the Generation R population‐based cohort. Eleven‐color flow cytometry was performed on peripheral blood samples to determine T and B cell subsets. The Child Behavior Checklist rated by parents was used to measure attention problems. Data were analyzed using linear regression analyses, adjusting for maternal and child covariates and co‐occurring childhood psychopathology. Results For T helper 1 (Th1) cells, one standard deviation (SD) increase was associated with 5.3% (95%CI 0.3; 10.5) higher attention problem scores. Furthermore, 1SD increase in CD8+ T cells was associated with 7.5% (95%CI 2.4; 12.7) higher attention problem scores. Within total CD8+ T cells, 1SD increase in naive or central memory cells was associated with 6.9% (95%CI 2.0; 12.1) and 6.4% (95%CI 1.5; 11.6) higher attention problem scores, respectively. No associations between Th2, Treg or B memory cells and attention problem scores were observed. Conclusion Higher Th1 and cytotoxic T cell numbers are associated with higher attention problem scores independent of co‐occurring psychopathology. This might indicate a possible role of a pro‐inflammatory immune profile in childhood attention problems.